Testing multi‐group measurement invariance of data from the knowledge creation practice inventory. (24th July 2018) - Jeong, Shinhee; Song, Jihoon; Hsiao, Yu‐Yu
Abstract : This study examined the extent to which the factor structure of the Knowledge‐Creation Practice Inventory (KCPI) is invariant across different occupational groups in South Korea, based on the studies of Song et al in 2011 and 2012. Inspired by Nonaka's (1994) knowledge‐conversion theory, the inventory consists of four dimensions (i.e., knowledge sharing, creating concepts, justifying concepts, and building prototypes), measured by 11 items. A total of 2, 364 responses collected from school teachers ( n = 1, 864), public‐sector employees ( n = 214), and private‐sector employees ( n = 286) were utilized to examine the measurement invariance, using a series of hierarchical multigroup confirmatory factor analyses. The results indicated that the four‐factor, 11‐item measurement model is equivalent across the three groups, supporting configural invariance, metric invariance, scalar invariance, and factor variance/covariance invariance, except factor mean invariance. A series of post‐hoc tests were additionally conducted to identify the factor mean differences among the three groups. Based on the results of this study, future researchers should use more diverse samples including a wide range of cultures or different subcultural groups (e.g., occupations, genders, and educational backgrounds) to expand the universality of the factor construct. Relevant organizations can utilize the inventory to assess their current capacity of knowledge creation and design for appropriate human resource (HR) or organizational development interventions to nurture and enhance employees' learning‐related behaviors. Since the generalizability and validity of the KCPI were supported in this study, at least among these three groups, more reliable, rigorous group comparisons are available for future research utilizing this inventory.